1995
DOI: 10.1038/eye.1995.118
|View full text |Cite
|
Sign up to set email alerts
|

How much blame can be placed on laser photocoagulation for failure to attain driving standards?

Abstract: One hundred consecutive patients who underwent bilateral pan-retinal photocoagulation (PRP) for proliferative diabetic retinopathy were assessed in accordance with the UK Driver and Vehicle Licensing Agency (DVLA) guidelines. Visual acuity was documented, and visual fields were assessed using the Esterman test. Among the 30% of patients who failed to reach the visual standards required for a driving licence, three groups were identified: those who failed to attain either the required binocular visual acuity (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…They advocated routine use of a 200-mm spot for primary PRP in PDR to achieve regression of PDR and maintenance of driving visual fields. Similar recommendations were reported by Mackie et al, 8 after 19% of patients studied were found to fail the DVLA standards. We used a 100-ms pulse duration, 300-mm spot, and low laser power.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…They advocated routine use of a 200-mm spot for primary PRP in PDR to achieve regression of PDR and maintenance of driving visual fields. Similar recommendations were reported by Mackie et al, 8 after 19% of patients studied were found to fail the DVLA standards. We used a 100-ms pulse duration, 300-mm spot, and low laser power.…”
Section: Discussionsupporting
confidence: 74%
“…The extent of visual field loss has been attributed to higher laser power intensity and greater retinal laser coverage. 8,9 In this study, an increase in mean threshold sensitivity was observed in a majority of the patients, and such increases were also present for the untreated central 101. Our laser technique was modelled on ETDRS guidelines but used lower power than did the EDTRS and Henricsson and Heijl studies, which may have contributed to significant functional benefits.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Both the present and a previous chairman emphasise that the recommendations should not be applied in an unduly restrictive manner. 4,8 Although fields that are found difficult to assess may be referred to the Visual Standards Sub-Committee, the majority of fields are not examined in this way. It is possible that variation in assessment may deprive some patients of their licence to drive whilst allowing others to continue despite having inadequate visual field.…”
mentioning
confidence: 99%